First microscopic and molecular identification of Cryptosporidium spp. in fat sand rats (Psammomys obesus) in Egypt and their potential zoonotic implications - Mohamed, Sara Abdel-Aal; Anwar, Fatma A. S.; Gareh, Ahmed; Ghallab, Marwa M. I.; Martínez, Remigio; Gouda, Asmaa Aboelabbas; Alajmi, Fatemah Enad; Alzaylaee, Hind; García-Bocanegra, Ignacio; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2025)
IntroductionRodents, thriving in human-altered environments, pose significant public health risks due to their role as reservoirs for numerous zoonotic parasites. Among these, Cryptosporidium spp. are recognized globally as leading causes of waterborne and foodborne diarrheal illnesses in humans. The specific role of fat sand rats (Psammomys obesus) in the transmission of Cryptosporidium spp. in Egypt and the genotypic characteristics of the circulating species in these animals remain poorly understood.MethodsIn this study, a total of 150 individual fat sand rat stool samples were collected from the saline marsh periurban areas of Abu-Rawash, Giza, Egypt. The samples were initially screened for the presence of Cryptosporidium spp. using light and scanning electron microscopy to characterize the parasite’s oocysts. Furthermore, molecular identification and characterization of the parasite were carried out on selected microscopy-positive samples (n = 30) using conventional polymerase chain reaction (PCR) targeting the Cryptosporidium oocyst wall protein (COWP) gene. A subset of these positive samples by PCR was subjected to sequencing, with the resulting sequences deposited in GenBank™ and analyzed through phylogenetic methods.ResultsConventional microscopy revealed that 46.7% (70/150; 95% CI: 38.7–54.6) of the analyzed stool samples contained structures consistent with Cryptosporidium oocysts. Moreover, the molecular analysis confirmed Cryptosporidium species in DNA from all 30 stool samples previously identified as heavily infected through microscopy. Notably, the phylogenetic analysis identified Cryptosporidium parvum (C. parvum) in the sequenced samples, likely originating from the rats’ native habitats. These identified species have been deposited in GenBank™ under the accession numbers OM817461 (C. parvum FSA-1), OM817462 (C. parvum FSA-2), and OM817463 (C. parvum FSA-3) and revealed closed genetic identity with those species reported from human and other animal species in the same geographic location.ConclusionOverall, this study represents the first morphological and genetic identification of C. parvum isolated from fecal samples of fat sand rats trapped from periurban areas in Egypt. These findings provide valuable insights into the potential zoonotic implications of rodents in disease transmission at the national level, offering crucial information for public health awareness campaigns and informing local authorities.